Minerals building blocks of the earth - Scott Resources Inc.; Miller, Eric (Writer); Scott Resources (Producer) ([s.l.] : Scott Resources Inc, 1992)
Described on the process of mining minerals
Narrator, Carol Brannam ; videography, Lawrence Jankowski
Keywords: Mines and mineral resources; Minerals -- Collection and preservation; Geology -- Colorado